Pyrimidine-Substituted Hexaarylbenzenes as Versatile Building Blocks for N–Doped Organic Materials - Meitinger, Nicolas; Mengele, Alexander K.; Nauroozi, Djawed; Rau, Sven (Organic Materials, 2021)
Hexaarylbenzenes (HABs) are valuable precursors for the bottom-up synthesis of (nano-)graphene structures. In this work the synthesis of several bis-pyrimidine substituted HABs furnished with tert-butyl groups at different sites of the four pendant phenyl rings is reported. The synthetic procedure is based on modular [4 + 2]-Diels–Alder cycloaddition reactions followed by decarbonylation. Analysis of the solid-state structures revealed that the newly synthesized HABs feature a propeller-like arrangement of the six arylic substituents around the benzene core. Here, the tilt of the aryl rings with respect to the central ring strongly depends on the intermolecular interactions between the HABs and co-crystallized solvent molecules. Interestingly, by evading the closest proximity of the central ring using an alkyne spacer, the distant pyrimidine ring is oriented in the coplanar geometry with regard to the benzene core, giving rise to a completely different UV-absorption profile.
Keywords: carbon materials; cycloadditions; Diels–Alder reactions; doping; ligand design; N-heterocycles